(untitled) (The Journal of Cultural Perspectives, 2025)
Any struggle for rights or reforms aims to influence decision-makers and political elite to achieve desired objectives. It is driven by specific groups or broad coalitions forming influential interest groups, pressure groups or large-scale movements. Each one of them has unique characteristics impacting outcomes. Given the context, assessing the potential success of recent Pakistani women’s struggle like the Aurat March demands careful analysis within a defined framework. While Pakistani women’s activism is historically established, the Aurat March’s artistic campaigns and wide appeal have notably advanced the fight for equal rights. However, its capacity to achieve lasting reforms in a religiously and patriarchally influenced society hinges on understanding its position within the spectrum of interest groups, pressure groups, and social movements. To classify the Aurat March and predict its future trajectory, this article uses content analysis approach to examine the Aurat March’s history, evolution, and core objectives of over time, utilizing both primary data (interviews) and secondary data (newspaper articles, journal articles and books).